ID: 142. Issue 1 (November 2015) - Ehrentraut, Stefan; Schneider, Björn; Nagel, Stefan; Eberth, Sonja; Kaufmann, Maren; Meyer, Corinna; Kadin, Marshall E.; Drexler, Hans G.; MacLeod, Roderick A.F.
<x xml:space="preserve">Abstract</x> SOCS-mediated control of JAK-STAT signalling orchestrates proliferation and differentiation. We describe the evolution of Th17 differentiation accompanying progression of a cutaneous T-cell lymphoma (CTCL) analysed in cell lines established at indolent (MAC-1) and aggressive (MAC-2A/B) disease phases. Cytogenetics and whole exome sequencing revealed genetic alterations in the JAK/STAT cascade and its suppressor SOCS1. All three cell lines show cytogenetic JAK2 activation combined with mutational activation of JAK3(V722I) and were conspicuously sensitive to selective inhibitors of JAK2 (TG101348) and JAK3 (tofacitinib). Despite shared genetic origins, indolent and aggressive phase cell lines displayed significant phenotypic differences, notably concerning phenotypic plasticity in response to treatment with IL-2, closely mimicked by IL-15, which was restricted to MAC-1 cells, confirming involvement of the shared IL2RB/IL2RG receptors. Treatment with IL-2 also induced IFNG-expressing multinucleated giant cells in MAC-1. IL-2 driven gene induction was abrogated by inhibition of both JAK3 (tofacitinib) and STAT5 (pimozide), implicating IL-2 in activating the IL2RG–JAK3–STAT5 cascade. Aggressive phase MAC-2A/B but not MAC-1 cells bore additional compound heterozygous SOCS1 mutations (G78R and D105N) conferring IL-2 resistance. Co-immunoprecipitation experiments showed that these SOCS1 mutations abolished interaction with JAK3, supporting a key role for SOCS1 in the suppression of activated JAK3–STAT5 signaling. This role was further evidenced by an IL-2-like inductive effect on gene expression following siRNA-mediated SOCS1 knockdown in MAC-1 cells. Collectively our findings show how disease progression-associated cytokine differentiation – itself counterintuitive – may be caused by mutations in a key pathway gene, SOCS1.